An Analytical Approach of Computational Complexity for the Method of Multifluid Modeling - Borah, A.K.; Singh, P. K. (Transactions on Engineering and Computing Sciences, 2015)
In this paper we deal the building blocks of the computer simulation of the multiphase flows. Whole simulation procedure can be viewed as two super procedures, the implementation of VOF method and the solution of Navier Stoke’s Equation, Moreover, a sequential code for a Navier Stoke’s solver has been studied.